DEVELOPMENT OF VOCATIONAL EDUCATION IN THE CONDITIONS OF WAR, POST-WAR RECOVERY, AND EUROPEAN INTEGRATION OF UKRAINE: NEW CHALLENGES AND OPPORTUNITIES (Innovative professional education, 2025)
The article analyzes the transformational processes in vocational education in Ukraine caused by the war, the need for post-war recovery, and the desire for European integration. Key challenges such as infrastructure destruction, changing labor market needs, and the need to adapt to European standards are considered. Special attention is paid to innovative approaches to learning, the development of digital skills, and cooperation with international partners
Keywords: vocational education, war, recovery, European integration, digitalization, innovation, international cooperation, labor market